Analisis Selera Konsumen Terhadap Atribut Produk dalam Keputusan Pembelian Minuman Mixue - Salma Aqila Putri; Hamidah Hendrarini; Dona Wahyuning Laily (Universitas Batanghari Jambi, 2023)
Mixue is an ice cream shop with cheap and delicious prices, making Mixue expand massively throughout Indonesia in a fairly short time. This study aims to identify and analyze the characteristics, purchasing decision process and consumer tastes towards the attributes of Mixue beverage products. This research was conducted at the Mixue shop in the Dharmawangsa and Ngagel Surabaya branches. The sampling technique was